Strategi Konten Payo Creative dalam Meningkatkan Brand Awareness Usaha Mikro Kecil Menengah Kuliner Fish in Fun dan Sushi Ryoku di Kota Palembang - Muhammad Rayhan Septian; Nurseri Hasnah Nasution; Muslimin . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
The rapid development of digital technology has significantly transformed communication and marketing practices in the business sector. Social media, particularly Instagram, has become an effective platform for Micro, Small, and Medium Enterprises (MSMEs) to promote their products while building brand awareness among consumers. This study aims to examine the Instagram content strategy developed by Payo Creative in enhancing brand awareness for culinary MSMEs, namely Fish in Fun and Sushi Ryoku, in Palembang City. The research focuses on the planning, implementation, and evaluation processes of the content strategies designed and executed by Payo Creative as the agency responsible for managing the digital communication activities of both businesses.This study employs a qualitative approach using a case study method to gain an in-depth understanding of the phenomenon under investigation. Data were collected through interviews, observations, and documentation, and were analyzed using data reduction, data presentation, and conclusion drawing techniques. The study is grounded in social media content strategy theory and the concept of brand awareness within the context of digital marketing communication.the findings reveal that Payo Creative implements various content strategies emphasizing storytelling, informative and educational content, consistent visual identity, and engaging copywriting. Furthermore, the utilization of Instagram features such as Reels, Stories, and Insights contributes to the effectiveness of message delivery to audiences. These strategies have succeeded in increasing audience engagement, strengthening brand image, and enhancing brand recognition among target consumers. The use of analytical data from Instagram Insights also assists in identifying content types that align with audience needs and preferences, enabling more effective marketing communication.This study concludes that Instagram content strategies that are creatively designed, consistently implemented, and data-driven play a significant role in improving brand awareness for culinary MSMEs. Payo Creative, as a creative agency, has proven effective in helping Fish in Fun and Sushi Ryoku establish stronger brand identities and foster closer relationships with consumers through social media. The findings of this study are expected to serve as a reference for MSME owners and digital marketing practitioners in developing effective communication strategies to strengthen brand positioning in the digital era